2019
DOI: 10.1021/acsami.9b07664
|View full text |Cite
|
Sign up to set email alerts
|

Facile Incorporation of “Aggregation-Induced Emission”-Active Conjugated Polymer into Mesoporous Silica Hollow Nanospheres: Synthesis, Characterization, Photophysical Studies, and Application in Bioimaging

Abstract: Typical aggregation-induced emission (AIE) luminogens tetraphenylethylene (TPE) and triphenylamine have been used to construct an AIE-active conjugated polymer, namely, poly­(N,N-diphenyl-4-(4-(1,2,2-triphenylvinyl)­styryl)­aniline) (PTPA), which consist of D−π–A architecture by Wittig polymerization. We fabricated mesoporous silica hollow nanospheres (MSHNs) which were encapsulated with the AIE-active polymer for applications in cellular imaging. It exhibits a positive solvatochromism effect by increasing sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 63 publications
1
24
0
Order By: Relevance
“…These features mean HMSNs represent ideal candidates for both the loading and delivery of chemical agents (e.g., carbon dots, organic dyes, fluorine compounds, etc.) [ 41 , 42 , 43 ]. HMSNs can be produced by several different methods—“soft-templating”, “hard-templating” and “self-templating” [ 44 , 45 ]—as illustrated by Figure 2 .…”
Section: Synthesismentioning
confidence: 99%
“…These features mean HMSNs represent ideal candidates for both the loading and delivery of chemical agents (e.g., carbon dots, organic dyes, fluorine compounds, etc.) [ 41 , 42 , 43 ]. HMSNs can be produced by several different methods—“soft-templating”, “hard-templating” and “self-templating” [ 44 , 45 ]—as illustrated by Figure 2 .…”
Section: Synthesismentioning
confidence: 99%
“…Using metallocene catalyst system, ethylene copolymer containing AIEgen monomer (VTBE) was obtained for the first time by olefin coordination polymerization. 13 C-NMR confirmed that the obtained polymer was a "real copolymer," not a mixture of ethylene homopolymer and VTBE. The molecular weight of the copolymer decreases with the increase of VTBE incorporation, and the molecular weight distribution accords with the characteristics of the polymer obtained by a typical single site catalyst.…”
Section: Discussionmentioning
confidence: 69%
“…Polymer Characterization: Solution 13 C NMR experiments were performed on a Bruker AVANCEIII-400 MHz spectrometer with a 10 mm PASEX 13 C-1 H/D Z-GRD probe. All sample solutions were prepared with 200 mg of the polymer material dissolved in 2.5 mL of 1,1,2,2-tetrachloro-1,2-dideuterioethane (C 2 Cl 4 D 2 ) in a 10 mm tube at 130-140°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations